Oscillation criteria for a nonlinear conformable fractional differential system with a forcing term (2020)
We employ the averaging functions, conformable fractional derivative and some inequalities to establish new oscillatory behaviour of the solutions of fractional differential system with a forcing term. The results obtained here extend and improve on some existing results. Examples are also given to show the validity of our results.